Modelling normal tissue toxicity in pancreatic chemoradiotherapy - Witztum, A (2018)
The relationship between radiation dose and toxicity in pancreatic chemoradiotherapy is not well understood. Clinically, excessive normal tissue toxicity is avoided by placing a constraint on the volume of the organ receiving a dose above a threshold. Dose-volume constraints lack spatial information which may be important in determining normal tissue response. Spatial dose distribution information can be found in dose-surface maps (DSMs). A dose-surface map is a 2-dimensional virtual unwrapping of the surface dose of on organ. Due to the complex geometry of the duodenum, previous methods for unwrapping tubular organs for spatial toxicity modelling are insuficient. A geometrically robust method for producing dose-surface maps, specifically for the duodenum, was created in order to characterise the spatial dose distribution. This unwrapping methodology was shown to be generalisable to simple organs such as the stomach, and extendable to more complex organs such as the bronchial tree. A graphical user interface to create dose-surface maps from organs in commercial treatment planning systems was also demonstrated. Duodenal and stomach dose-surface maps were created for patients from two pancreatic chemoradiotherapy trials, ARCII and SCALOP, treating locally-advanced pancreatic cancer (LAPC). New spatial features were extracted from dose-surface maps and their correlation with upper-gastrointestinal toxicity quantified and compared to traditional dose-volume metrics. The predictive power of some of these new metrics were found to be superior to dose-volume metrics in the stomach, but no significant correlation was found in the duodenum. Duodenal motion throughout treatment occurs both due to respiratory motion and peristalsis. On board imaging using cone-beam CT (CBCT) during individual treatment fractions shows that interfraction variability is non-systematic and cannot be predicted. While abdominal compression is able to restrict some interfraction motion, it is unable to control peristaltic changes. Accumulated duodenal dose-surface maps from these images were created to investigate the differences between the planned and delivered dose.